Understanding Breast Implant Illness: Etiology is the Key. (19th April 2021) - Yang, Siling; Klietz, Marie-Luise; Harren, Anna Katharina; Wei, Qiang; Hirsch, Tobias; Aitzetmüller, Matthias M
Abstract: Because breast augmentation is one of the most popular cosmetic procedures, the issue of implant-related complications has been widely debated ever since the FDA approved the use of implants in 1962. Although decades have passed, breast implant illness (BII) still represents a poorly defined and controversial complication. With ongoing nonscientific discussion in the mainstream media and on social media, revealing the etiology of BII is urgent because knowledge of this subject ultimately influences patients' decisions. Little or no scientific research is currently available on BII and no final conclusions regarding its etiology, clinical manifestations, diagnostic criteria, or treatment have been made. This review aims to give an overview of the hypotheses on the etiology of BII and seeks inspiration to improve the conditions of BII patients.